(untitled) (Human Factors in Design, 2023)
The objective of this work is to present the creation of a videobook with LIBRAS animation, focused on Inclusive Education. The study developed educational material for learning LIBRAS, as well as promoting healthy eating habits. The construction of the videobook involved the following steps: defining the theme, plot, and script; creating characters and storyboards; modeling the scenery and characters; animation; recording LIBRAS; designing the page layout and assembling the videobook. In a future stage, it is expected to validate the material with users to assess its effectiveness and contribution to Inclusive Education.